2013
DOI: 10.18697/ajfand.59.10975
|View full text |Cite
|
Sign up to set email alerts
|

Profitability and economic efficiency of groundnut production in Benue state, Nigeria

Abstract: There has been a remarkable reduction in the contribution of groundnut to Nigeria’s foreign exchange earnings since the discovery of petroleum resources. There is need to re -position this valuable crop to assume its rightful position in the nation’s economy. Thus, this study assessed the profitability of groundnut production and level of technical and allocative efficiencies of the farmers using Benue State as a case study. Multi -stage sampling technique, which involves purposive selection of two Local Gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The profit elasticity with respect to the price of seed (β1 = 0.17, p>0.1) and labour (β5 = 0.41, p>0.1) were positive and statistically insignificant, which suggests that they were not important determinants of profit. The finding is contrary to expectation (Ani et al, 2013;Wongnaa et al, 2019), but consistent with Mailena et al (2013) who found that the price of seed and labour did not influence profit among rice farmers in Malaysia. The effect of the price of inorganic fertilizer was negative and significant at 1% level of probability (β2 = -0.75, p<0.01), which means that if the price of inorganic fertilizer increases by 1%, profit will decrease by 0.75%, holding other variables constant.…”
Section: Profit Efficiency Differential Between Bb-sri and Fpsupporting
confidence: 67%
“…The profit elasticity with respect to the price of seed (β1 = 0.17, p>0.1) and labour (β5 = 0.41, p>0.1) were positive and statistically insignificant, which suggests that they were not important determinants of profit. The finding is contrary to expectation (Ani et al, 2013;Wongnaa et al, 2019), but consistent with Mailena et al (2013) who found that the price of seed and labour did not influence profit among rice farmers in Malaysia. The effect of the price of inorganic fertilizer was negative and significant at 1% level of probability (β2 = -0.75, p<0.01), which means that if the price of inorganic fertilizer increases by 1%, profit will decrease by 0.75%, holding other variables constant.…”
Section: Profit Efficiency Differential Between Bb-sri and Fpsupporting
confidence: 67%
“…It has been observed that the educational level of the respondents greatly assist in understanding the different tasks that are involved in cassava processing. The educational attainment of an individual does not only raise his performance, but also increase his ability to understand and evaluate information on new methods and process being disseminated through extension service (Ani et al, 2013). Also level of education of respondents has been tied to the rate of adoption of innovation (Owa et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Onuche and Oladipo (2020) found an allocative efficiency of 1.38 in a study in Kogi state. Similarly, Ani et al (2013) reported an allocative efficiency estimate of 1.275 for groundnut farmers in Benue. Thus, the estimates found here imply that Fadama III had elicited significant improvement in resource allocation by farmers in Kogi state.…”
Section: Allocative Efficiency Estimates Of Beneficiaries and Non-ben...mentioning
confidence: 99%